Peran Media Sosial Dalam Menyebarkan Pesan King of Sparko Tentang Pentingnya Berolahraga - Mutaqin, Rizal; Dharmawan, Eka Wira; Dharmopadni, Dwi Shinta; Mutaqin, Ghani (Jurnal Surya, 2024)
This research investigates the role of social media in spreading King of Sparko's message about the importance of exercise and its impact on the exercise behavior of Indonesian people. This research adopts a qualitative approach by collecting data through in-depth interviews and social media content analysis. The research results show that social media plays an important role in supporting the King of Sparko campaign. Creative visual content, such as images and videos, has proven effective in attracting attention and motivating followers to exercise. Campaigns that engage followers in contests and challenges are successful in increasing community engagement and participation. In addition, messages emphasizing the physical and mental health benefits of exercise successfully influence people's perceptions and behavior. The King of Sparko campaign has helped raise people's awareness of the importance of exercise and motivated them to start or increase their physical activity. The implication of the results of this research is that social media has great potential as an effective health promotion tool. Future health campaigns could consider strategies that engage followers, emphasize health benefits, and use engaging visual content to influence people's behavior in favor of an active and healthy lifestyle.